2013
DOI: 10.1021/cm401762g
|View full text |Cite
|
Sign up to set email alerts
|

Competitive I2 Sorption by Cu-BTC from Humid Gas Streams

Abstract: Competitive sorption of molecular iodine gas from a mixed stream containing iodine and water vapor is identified and characterized for the hydrophilic Cu-BTC metal–organic framework. By combining simulation (Grand Canonical Monte Carlo and molecular dynamics simulations) with crystallography (high-energy synchrotron-based powder X-ray diffraction data and pair distribution function analyses), we show that I2 substantially adsorbs, in preference to water vapor, into two principal areas. First, it adsorbs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
220
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(238 citation statements)
references
References 34 publications
18
220
0
Order By: Relevance
“…150 Interestingly, Nenoff et al found that HKUST-1 also possesses properties that are relevant to nuclear energy industrial processes. 156 Despite the hydrophilic nature of the structure the authors found molecular iodine, a long-lifetime product that is released during the processing of spent nuclear fuel, is preferentially adsorbed over water in HKUST-1 under 1:1 I 2 :H 2 O conditions. This behavior was attributed to the formation of hydrophobic I 2 barriers in the structure which reduce water's ability to adsorb into the pores.…”
Section: Multicomponent Adsorptionmentioning
confidence: 98%
“…150 Interestingly, Nenoff et al found that HKUST-1 also possesses properties that are relevant to nuclear energy industrial processes. 156 Despite the hydrophilic nature of the structure the authors found molecular iodine, a long-lifetime product that is released during the processing of spent nuclear fuel, is preferentially adsorbed over water in HKUST-1 under 1:1 I 2 :H 2 O conditions. This behavior was attributed to the formation of hydrophobic I 2 barriers in the structure which reduce water's ability to adsorb into the pores.…”
Section: Multicomponent Adsorptionmentioning
confidence: 98%
“…the host-guest correlations. Furthermore, the intensity of the PDF peaks is correlated to the relative abundance of a given atom-atom pair: thus the intensity of the peaks due to Cu-O and I-I bonds (at about 2 and 2.7 Å, respectively) provides an estimation of the Cu/I ratio which is monitored during the room temperature isotherm for iodine sorption, as reported in Figure 11 43 .…”
Section: Hydrogen Storage Materialsmentioning
confidence: 99%
“…[102][103][104][105][106][107][108] Interestingly, when the robust solvent-free framework I was immersed into a solution of iodine in cyclohexane, its hexagonally-arranged channels allowed iodine to form very intriguing polyiodine chains. The iodine-captured framework of I, I_I 2 , was structurally characterized by X-ray crystallography ( Table 1).…”
Section: Characterization Of Current-voltage (I-v)mentioning
confidence: 99%